Masjid as an Institution of Reforming Almajiri Education System: A Policy Option for State Governments in Northern Nigeria - Saidu Ahmad Dukawa; Abbo Usman; Umar Jibrilu Gwandu (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
One of the critical issues bedeviling the Muslim community in Northern Nigeria is the current trend of the Almajiri system of education where children at tender age are made to excruciatingly fend for themselves in the name of search of Islamic knowledge. This has become a source of concern as the children are not only deprived of their basic rights of healthy and decent living, but are also prone to many misdemeanors. Numerous governmental and (non-) faith-based organizations have been struggling to transform the system. This paper highlights the crucial role of Masaajid as a rallying point for Muslims; for prayers, study cycles, holding meetings, conflict resolution, contracting marriages, offering charity, provision of shelter to the destitute, among others. Hence, the paper brings into limelight ways in which Masaajid in Northern Nigeria can be used through zakah and waqf, contribution of philanthropists and other stakeholders in reforming the Almajri system of education through the use of masaajid as alternative school system thereby implementing better ways of eradicating the scourge. The paper concludes that masaajid provide veritable alternatives for result-oriented learning in serene and descent atmosphere devoid of inhumane treatment and in conformity with the pristine teachings of Islam.